Akibat Hukum Wanprestasi atas Pembatalan Sepihak dalam Perjanjian Pengikatan Jual Beli (PPJB) Kasus Dokter SM di Palembang - Ashhifa Roqiiqulqolby; Jenar Satria Annur Sidiq; Tsulistiyani Nur Islami (Letterlijk, 2025)
The Sale and Purchase Agreement (PPJB) is a form of preliminary agreement used to regulate the legal relationship between the seller and the buyer prior to the official transfer of ownership through a Deed of Sale and Purchase (AJB). Whether executed in authentic form or under private hand, the PPJB gives rise to legally binding rights and obligations. This article discusses the legal aspects of PPJB, the concept of breach of contract (wanprestasi), and analyzes a case involving unilateral cancellation by Dr. SM in Palembang, which is classified as a breach of contract. The cancellation not only violates the principle of pacta sunt servanda, but also causes material losses to the buyer (TW). In its resolution, Indonesian law—through the Civil Code (KUHPerdata)—provides a legal basis for the aggrieved party to claim compensation and protect their rights. This study emphasizes the importance of executing agreements in good faith, the role of notaries in drafting deeds, and the need for preventive legal supervision to avoid losses due to breach of contract.